MEDICATION NON-ADHERENCE IN UNCONTROLLED HYPERTENSION: SELECTIVE DETECTION AND EFFICIENCY AND EFFECTIVENESS OF A PROGRAM TO IMPROVE COMPLIANCE (ATHAN TRIAL). (June 2022) - Oliveras, Anna; Galceran, Isabel; Camps, Carme; Faura, Anna; Pascual, Sergi; Fontdevila, Laia; Vazquez, Susana
Abstract : Objective: To assess whether the implementation of a specific action plan to improve adherence for 3 months results in reduced peripheral 24h-systolic blood pressure (SBP) in patients with resistant hypertension (RH) or uncontrolled hypertension with at least 2 drugs. Design and method: Interventional, prospective, randomized, controlled, parallel groups, open study of patients consecutively attended in a specialized Hypertension Unit with ambulatory 24h-BP equal or more than 130 and/or 80mmHg although receiving at least 2 antihypertensive drugs. The partially or completely non-adherent patients (confirmed by determination of antihypertensive drugs in urine) were randomized (1: 1) to receive a specific program to improve adherence (intervention group) or routine follow-up (control group), with determination of antihypertensive drugs in urine, office-BP measurement and 24h-ambulatory BP monitoring at pre-randomization and 3 months. Results: Forty-three patients were randomized (mean age 59+/-14yr, 70% male). Mean+/-S.D. baseline SBP/DBP(mmHg) were 150.4+/-17.1 and 90.7+/-15.5, and the number of prescribed non-detected drugs in urine was 2+/-1.4. At 3 months, the variation of SBP-24 h for the intervention group and the control group was (mean[95%CI]) = -14.3 mmHg (-20.5 to -8.1), p < 0.001 and -3.3 mmHg (-10.2 to 3.7), p = 0.339, respectively. See table. At 3 months, the variation of the number of non-detected antihypertensive drugs in urine was (mean[95%CI]) = -1.29 mmHg (-2.06 to -0.53), p = 0.002 and -0.53 mmHg (-1.26 to 0.2), p = 0.144, respectively. Conclusions: A specific nursing intervention to improve therapeutic adherence results in an improvement of BP control in patients with difficult-to-control hypertension and inadequate therapeutic compliance.